Autoantibodies, cutaneous subset and immunosuppressants contribute to the cancer risk in systemic sclerosis - Maria De Santis; Carlo Selmi; Angela Ceribelli; Stefanos Bonovas; Francesca Motta; Antonio Tonutti; Natasa Isailovic; Rita Ragusa; Emanuele Nappi (RMD Open)
Objective Systemic sclerosis (SSc) is associated with an increased risk of cancer. We aimed to assess the prevalence of cancer in our cohort and to explore possible associations with clinical, immunological and treatment characteristics.Methods Our retrospective monocentric cohort study of patients with SSc recorded prevalent and incident cases of malignancy, including those diagnosed within 3 years of the SSc onset (defined as cancer-associated scleroderma) and sought associations with the clinical characteristics and the serum autoantibody profiling performed using RNA and protein immunoprecipitation, Western-blot, immunoblot and ELISA at the time of SSc diagnosis, prior to any specific treatment.Results Among 290 patients with SSc, the overall prevalence of cancer was 20%, with 8% of cases being cancer-associated scleroderma. Both conditions were more frequent in elderly patients and in patients with positive anti-Ro52 or anti-U3-RNP. Cancer-associated scleroderma was significantly more prevalent among patients negative for both anti-centromere (ACA) and anti-topoisomerase-1 (TOPO1) antibodies, especially in the case of diffuse SSc. Immunosuppressants were not significantly associated with cancer. Patients triple negative for ACA, TOPO1 and anti-RNA polymerase III antibodies had a significantly higher risk of breast cancer.Conclusions Cancer surveillance should be particularly careful in patients with diffuse SSc, increased age at disease onset and without classical SSc-related autoantibodies.